Addressing the Problem of Harmful Algal Blooms in Latin America and the Caribbean- A Regional Network for Early Warning and Response - Cuéllar Martínez, Tomasa del Carmen (2018)
Harmful algal blooms (HABs) constitute a worldwide problem, affecting aquatic ecosystems, public health and local economies. Supported by the International Atomic Energy Agency since 2009, Latin America and the Caribbean (LAC) countries, including Brazil, Chile, Colombia, Costa Rica, Cuba, Dominican Republic, El Salvador, Guatemala, Haiti, Mexico, Nicaragua, Panama, Uruguay and Venezuela, have integrated a regional network for early warning of HABs and biotoxins in seafood. Technical capacities have been developed at regional level to identify toxic species, evaluate biota toxicity, and to perform retrospective analysis of HAB occurrence. This network involves 58% of the coastal LAC countries, two regional reference centers (in El Salvador and Cuba), 14 well equipped institutions, and 177 professionals trained to contribute to the operation of HAB and biotoxin monitoring programs. All countries from the network have reported planktonic and benthic toxic species, and in selected cases, associated with toxin in biota. Dinocyst abundance analysis in 210Pb-dated sediment cores have shown that some harmful species have been present in the region for at least 100 years ago, and that both coastal water pollution and climate change are important drivers for HAB occurrence. Efforts must be made to enrich the data base records on HAB events occurred in LAC, better understand key environmental variables that control HABs and expand coverage of HAB monitoring to all coastal countries in LAC to promote sustainable development of the region.